2002
DOI: 10.2208/journalam.5.543
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil-structure interaction on pounding response of adjacent buildings due to near-source earthquakes

Abstract: A numerical approach to analyse pounding responses of adjacent buildings on subsoil to earthquakes is presented. The nonlinear calculation of the soil-structure system is performed subsequently in the Laplace and the time domain. The adjacent buildings and the subsoil are described by finite elements and boundary elements, respectively. In the numerical investigation the effect of Kobe, Northridge and Chi-Chi near-source earthquakes is considered. The result reveals that both the subsoil and long-period pulses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 13 publications
(4 reference statements)
2
20
0
Order By: Relevance
“…(2) The short duration and high magnitude of acceleration pulses are caused by pounding at 20th floor of building A. It is observed that higher frequency content of acceleration increases at 20th floor of building A from Figure 11b,d,f, which is consistent to the conclusion by Chouw [37]. (3) The acceleration response of PILE_P considering SSSI in pounding case, is greater than that of FIXED_P, which does not take SSSI into consideration in the pounding case.…”
Section: Acceleration Response Of Superstructuresupporting
confidence: 86%
“…(2) The short duration and high magnitude of acceleration pulses are caused by pounding at 20th floor of building A. It is observed that higher frequency content of acceleration increases at 20th floor of building A from Figure 11b,d,f, which is consistent to the conclusion by Chouw [37]. (3) The acceleration response of PILE_P considering SSSI in pounding case, is greater than that of FIXED_P, which does not take SSSI into consideration in the pounding case.…”
Section: Acceleration Response Of Superstructuresupporting
confidence: 86%
“…The result coincided exactly with the one obtained using a step-bystep numerical integration procedure directly in the time domain [24]. To demonstrate the reliability of the procedure in estimating the relative response of structures with pounding the example presented in [9] is analysed using the present method and the program DRAIN-2DX [25].…”
Section: Validation Of the Nonlinear Analysissupporting
confidence: 53%
“…The procedure is repeated until no more pounding or separation takes place. The nonlinear procedure for analysing the soil-structure system in Laplace and time domain is explained in detail in [24]. It should be noted that this approach of pounding force modeling is believed more accurate than using an additional impact element consisting of spring and dashpot, since it considers the correct distribution of the whole mass and stiffness of the adjacent structures in the calculation of the structural responses with pounding whereas using an impact element considers only the relative girder displacement and the axial stiffness of one bridge girder.…”
Section: Non-linear Analysis In Laplace and Time Domainmentioning
confidence: 99%
“…Laplace transform method [Chouw, 2002;Chouw and Hao, 2008a] incorporates the influence of pounding in Laplace and time domains by formulating the nonlinear behavior in an increment way. Within every increment the system is assumed to behave linearly, and the transform approach is applied.…”
Section: Laplace Transform Methodsmentioning
confidence: 99%
“…This out-of-phase movement of adjoining bridge segments can result from many reasons, e.g. the differences in their dynamic characteristics, the nonuniform excitations at their supports and the interaction between the structure and the surrounding soil [Chouw andHao, 2005, 2008a]. There are many reasons that may result in the spatially varying ground motions such as the wave passage effect results from the different arrival times of waves at different locations, coherency loss effect owing to seismic waves scattering in the heterogeneous medium of the ground and site amplification effect due to different local soil properties [Der Kiureghian, 1996].…”
Section: Numerical Simulation Of Pounding Responsesmentioning
confidence: 99%